MENJADI PENDIDIK IDEAL DI LINGKUNGAN SEKOLAH DAN DI KALANGAN MASYARAKAT - Prastyawan Prastyawan (Al Hikmah: Jurnal Studi Keislaman, 2016)
Status and strategic role also held by teachers, especially in efforts to form a national character through the development of personality and values as desired. The dimensions of the position and role of teachers is difficult replaced by others. Viewed from a dimension of learning the role of teachers in Indonesian society remains predominant even technology that can be utilized in the learning process sometimes still very classic and far from modern. In this case the teacher has to be a change agent capable of promoting understanding and tolerance, and not just mencerdasakan learners but was able to develop a complete personality, morals, and character. For this purpose, it is necessary ideal and knowledgeable teachers who have sufficient competence and professionally accountable. In addition, for teachers to be accepted and recognized in the community of teachers should be able to be a role model for them is reflected in the behavior and daily activities, teachers should also be able membuktikann to all the people of the attitude of professionalism as a teacher, so the teacher profession is slowly and spontaneous be recognized by society. And in Muslim society, teachers must also be able to be a pioneer in any religious activities, both individually and collectively. Teachers are also responsible for the harmonious relationship of the school and community.